Najpogostejše poškodbe gležnja in stopala ter gibalno-terapevtski pristopi k preventivi in zdravljenju - Benčan, Žiga (Šport (Ljubljana), 2017)
Injuries of ankle and foot are among the most common musculoskeletal disorders. These injuries are often result from damage to the ligament structures of ankle. The most common mechanism of injury is foot inversion with the plantar flexion. The consequences are pain, swelling, functional limitations and absence from activity in sports. Reinjury is often associated with a chronic ankle instability. The purpose of this article was review of kinesiotherapeutic interventions which prevent chronic injuries of ankle and foot. We reviewed the articles of three common interventions. Based on results from studies we have found that ankle stability training improves joint position sense and it is an effective preventive method on reducing ankle ligament injuries. Stability training includes proprioception exercises of which goal is establishing balance on unstable surfaces. Exercises with resistance bands are the most common method of ankle strength training. We have found that ankle strentgh development is associated with improvements in perceived ankle stability and functional outcomes. Long-term and prevention effects of strength training are lacking. Studies evaluated that use of prophylactic ankle braces and bandages, reduced the incidence of acute ankle injuries. Protective effect was observed in athletes both with and without a previous history of ankle ligament injury.
Keywords: ankle brace; ankle sprain; jakost; joint stability; opornice; sklepna stabilnost; sport; strength; šport; zvin gležnja